Analysis of Regional Government Financial Management Performance in Banggai Islands Regency, 2021–2025 - Liswan Rusman; Umar; Mastia M Halimu (Universitas Muhammadiyah Palu, 2026)
This study aims to analyze the performance of regional revenue and expenditure management in Banggai Islands Regency during the 2021–2025 period. The study employed a descriptive quantitative approach by analyzing the Regional Government Financial Statements (LKPD) for 2021–2025. The data were obtained from the Regional Revenue, Finance, and Asset Management Agency (BPKAD) of Banggai Islands Regency and analyzed using indicators including the fiscal independence ratio, regional financial efficiency ratio, growth ratio, effectiveness ratio, variance analysis, and expenditure harmony ratio. The results show that the level of fiscal independence was low, while regional financial efficiency was categorized as less efficient. The growth of regional revenue and expenditure fluctuated during the study period. Regional revenue effectiveness was categorized as moderately effective. The expenditure variance resulted in a negative variance, while the expenditure harmony ratio indicated that significant disparities remained among the components of regional expenditure.